Effect of Surface Treatment of Two Ceramic Materials by Er,Cr:YSGG Laser Irradiation on The Shear Bond Strength to Resin Cement “A Comparative in-Vitro Study” - Mandil, Shahd Taha; Katamish, Hesham; Salah, Tarek (Brazilian Dental Science, 2020)
Objective: The aim of this study is to assess the effect of Er,Cr:YSGG laser on the shear bond strength (SBS) and surface topography of two CAD/CAM ceramic materials bonded with self-adhesive resin cement. Material and methods: sixty ceramic CAD/CAM discs were obtained, 30 lithium disilicate (IPS Emax) and 30 hybrid resin ceramic (Vita Enamic). The Slices were allocated into six groups (n=10) according to ceramic material and surface treatment; Group (LD-C): IPS Emax treated with 9% hydrofluoric acid(HF), Groups (LD-P1) and (LD-P2): IPS Emax treated with Er,Cr:YSGG laser with parameters 1.5 W and 2.5 W, respectively. Group (RC-C): Vita Enamic treated with 9% hydrofluoric acid (HF), Groups (RC-P1) and (RC-P2): Vita Enamic treated with Er,Cr:YSGG laser with parameters 1.5 W and 2.5 W, respectively. All samples were cemented with self-adhesive resin cement and thermocycled for 5000 cycles. The SBS was measured using a universal testing machine and the mean values (MPa) were analyzed using Two-way (ANOVA) (P ? 0.05) and Bonferroni’s post-hoc test. Results: RC-C (16.55) showed highest SBS followed by LD-C (13.79), which revealed no statistically significant difference with RC-P1 (12.33) and RC-P2 (11.2). The lowest SBS values were found with LD-P1 (2.7) and LD-P2 (2.1). SEM analysis revealed Vita Enamic to have the highest surface roughness. Fracture pattern analysis showed adhesive failure with IPS Emax groups and mixed failure with Vita Enamic groups. Conclusion: Er,Cr:YSGG laser irradiation with the parameters used did not increase SBS of IPS Emax and Vita Enamic with composite resin compared to HF acid etching.KeywordsEr,Cr:YSGG laser; Shear bond strength; Surface treatment; Ceramic materials.